Hello, good-bye - Alda, Arlene, 1933- (Plattsburgh, N.Y. : Tundra Books of Northern New York, 2009)
A series of photographs introduces sets of opposites, such as straight and slanted, soft and hard, and push and pull.
Booklist.
Kirkus Review.
Resource Links.
K-3
Keywords: English language -- Synonyms and antonyms -- Juvenile literature; English language -- Synonyms and antonyms; English language -- Synonyms and antonyms